A cognitive occupation-based programme for people with multiple sclerosis: A new occupational therapy cognitive rehabilitation intervention - Hynes, Sinéad M (Hong Kong J Occup Ther, 2019)
INTRODUCTION: Cognitive difficulties have been reported to have the greatest effect on function and quality of life in people with multiple sclerosis, affecting 50–60% of people. To date, few interventions have been developed to treat cognitive issues in multiple sclerosis. Here we report on a Cognitive Occupation-Based programme (COB-MS) for people with Multiple Sclerosis an evidence-based intervention to address everyday problems encountered due to cognitive difficulties. The aim of this research was to explore the views of people with multiple sclerosis and occupational therapists on the programme and its potential implementation in practice. METHODS: Data were elicited from a purposive sample of 12 people from two stakeholder groups, people with multiple sclerosis (n = 5) and occupational therapists (n = 7), through focus groups and interviews. The programme and related materials were presented, and contributions recorded, transcribed and thematically analysed. RESULTS: Two main themes were identified from analysis of the data: response to the intervention and challenges to implementing the programme. Occupational therapists agreed that the COB-MS is client-centred. People with multiple sclerosis thought that it was a validating intervention. The overall format was viewed to be useful and feasible. CONCLUSION: The COB-MS for people with Multiple Sclerosis is the first known cognitive intervention using an occupation frame of reference to address difficulties faced among persons with multiple sclerosis and was found to be timely and relevant to the needs of the population.